An investigation into constraints impacting on small micro and medium enterprises (SMMEs) access to finance in Buffalo City Metropolitan Municipality - Dlova, Mzwanele Roadwell (Rhodes University, Faculty of Commerce, Rhodes Business School, 2012)
Internationally, in both developed and developing countries, it has been accepted that SMMEs are the backbone and the driving force of economic growth and job creation. In South Africa, SMMEs account for approximately 60 per cent of all employment in the economy and more than 35 per cent of South Africa's Gross Domestic Product (GDP) (Ntsika, 1999:38; Gumede, 2000:67 and Berry et ai, 2002 in Kongolo, 2010:235). SMMEs are often the vehicle by which the lowest income people in our society gain access to economic opportunities. The sector represents 97.5 per cent of the total number of business firms in South Africa and that it contributes 42 per cent of total remuneration. SMMEs account for some 3.5 million jobs and have between 500 000 and 700 000 businesses (Abor and Quartey, 2010:2337). Due to the above-mentioned contribution, the South African government initiated a number of SMME support programmes aimed at promoting, growing and developing the SMME sector. As a result, a number of national government agencies such as the National Youth Development Agency (NYDA), Khula Finance Limited, the National Development Agency (NDA), the Small Enterprise Development Agency (SEDA) and many other national , provincial and local government organizations were established post 1994. However, despite the concerted efforts by government to develop the sector, SMMEs are, after 17 years of democracy, still faced with enormous challenges such as access to markets, information, appropriate technology, finance, to mention but a few. Of the above-mentioned challenges, access to finance is on top of the list of these. This study, therefore, is aimed at investigating external, institutional and internal constraints impacting on SMME access to finance in the Buffalo City Metropolitan Municipal area. The study is also aimed at ascertaining which of the abovementioned constraints have the greatest influence to SMME access to finance. In developing the framework of the study, recent empirical research conducted around the country and internationally on constraints influencing SMME access to finance (Bbenkele, 2007:18; Ganbold, 2008:45; Mahadea and Pillay, 2008:99; Chenesai, 2009:135; Zindiye, 2009:78; Fatoki and Garwe, 2010:2765; Pandula, 2011 :257) was drawn upon. In order to meet the objectives of the study, a simple random sample survey of 50 SMMEs in the Buffalo City Metropolitan Municipality (BCMM) jurisdiction was conducted. The profile of the SMMEs was very similar to that of other studies that focused on constraints to SMME access to finance. A structured questionnaire was used to collect data from SMME owner-managers and a response rate of 60 percent was achieved . The results of the study indicated that the high cost of credit and interest rates and Value Added Tax (VAT) registration were the key external factors that impacted on SMME access to finance. Generally, SMMEs are viewed by lending institutions as high risk category. Therefore, even though interest rates have come down significantly, the cost of credit and interest rates still remain a constraint. The study also found that even though the South African Revenue Services (SARS) has increased the VAT threshold to R1 million (South African Revenue Service, 2007: 29), SMMEs still struggled to register for VAT. With regards to the institutional factors, the study revealed that ineffective support services provided by private and public SMME support agencies, the lack of communication of these services (access to information) and the lack of the subsequent follow-up services were the key constraints to SMME access to finance. The results of the study indicate that those firms with good track record, high annual turnover, sophistication and diverse skills, good credit record, good cash flow, proper financial records, bankable and viable business plans, collateral and registered for VAT were more likely to have access to finance than their counterparts. The main conclusion of the study is that the internal factors turned to have the greatest influence to SMME access to finance. However, there is more to be done by private and public SMME support agencies and lending institutions to address the above-mentioned institutional constraints which have a negative influence to SMME access to finance. It is recommended that more in-depth empirical research be conducted on the support services provided by private and public SMME support agencies in terms of the services that they offer the effectiveness of the services and how these are communicated to potential customers. It is also recommended that training workshops aimed at addressing the intemal constraints identified be conducted. Also recommended is the development and implementation of sector-specific mentoring programmes for the owner-managers. Strategies to improve the awareness of support services provided by SMME support agencies need to be developed. This would ensure the effective use of these services by SMMEs. It is also recommended that SMME support agencies and lending institutions staff be trained in order to better understand and be more responsive to the owner managers' needs. Linkages with tertiary institutions in planning and conducting the training needs to be made.
Keywords: Small business -- South Africa -- East London; Small business -- Finance -- South Africa -- East London